2017
DOI: 10.1007/s00170-017-0155-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of multi-point forming process parameters

Abstract: The need for sheet metal forming using reconfigurable dies has increased due to rapid changes in part design to meet customer requirements, especially in the automotive industry. Reconfigurable dies have relatively low manufacturing cost compared with solid dies, and the same tool can be readily changed to produce different parts. Previous investigations have focused on avoiding defects without taking into account the effects of process on the quality characteristics of fabricated parts. This study investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…The tensile test results are shown in Fig In addition to the experimental data, a power law equation was also applied to represent the stress of the sheet material (see Eq. 1) [2].…”
Section: Experimental Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The tensile test results are shown in Fig In addition to the experimental data, a power law equation was also applied to represent the stress of the sheet material (see Eq. 1) [2].…”
Section: Experimental Workmentioning
confidence: 99%
“…The mechanical properties of the DC05 sheet material are shown in Table 1. A mesh-type elastic cushion was prepared using polyurethane A-90 as it is one of the durable materials used in the MPF process [2]. Table 2 shows the solid and mesh-type elastic cushions used in the experiments.…”
Section: Experimental Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For AA6082-T6 used in the study, = 290 MPa, K = 151.1 MPa and N = 0.684 at room temperature, which were obtained by fitting Eq. (14) to room temperature tensile test data of AA6082, as shown in Fig. 6.…”
Section: Test Blankmentioning
confidence: 99%
“…[12,13]. The effect of thickness [14], hardness [15] and materials [16] of elastic cushions on formed quality of test blanks with MPF tool has been investigated and the results indicated that a higher forming shape accuracy can be achieved by elastic cushions with smaller thickness and greater hardness. However, the thickness of elastic cushions should be above a critical value to avoid apparent dimples in formed blanks [17].…”
Section: Introductionmentioning
confidence: 99%